An investigation of bonding systems for the polycarbonate crown restoration - Wiggins, C E; Caputo, A A; Jedrychowski, J R (The Journal of the American Dental Association (1939), 1978)
Tensile retentive strengths for six polycarbonate crown cementation systems were examined with use of extracted human teeth prepared with and without retentive grooves. From the results of this study, use of unfilled intermediary resins followed by polycarboxylate or zinc phosphate cements is recommended. Retentive grooves did not contribute to overall retention.